Microfibrillated cellulose molded body
Patent Information
- Application Number
- JP2024071194
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2043-09-13
Smart Images

Figure 2025041509000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to microfibrillated cellulose bodies. [Background technology]
[0002] A high-strength material using cellulose microfibrils is disclosed in Japanese Patent No. 3641690 (Patent Document 1). Also, a method for producing a molded article of microfibrillated cellulose is disclosed in Japanese Patent Laid-Open No. 2009-96167 (Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 3641690 [Patent Document 2] JP 2009-96167 A Summary of the Invention [Problem to be solved by the invention]
[0004] Microfibrillated cellulose molded bodies, which have relatively high strength, are used in various environments, but high dimensional stability is required for the microfibrillated cellulose molded bodies. Of course, it is desirable that the materials used, taking into consideration environmental resistance, contain as few substances as possible other than microfibrillated cellulose. The techniques disclosed in the above-mentioned Patent Documents 1 and 2 have difficulty in dealing with such problems.
[0005] Therefore, one of the objects is to provide a microfibrillated cellulose molded article that has good environmental resistance and can achieve high dimensional stability. [Means for solving the problem]
[0006] The microfibrillated cellulose molded article according to the present disclosure is composed of microfibrillated cellulose and melamine resin. The content of the melamine resin is 20.0 mass% or more. The water absorption rate when immersed in water at 20°C for 24 hours is 1.6% or less. Effect of the Invention
[0007] Such a microfibrillated cellulose molded article has good environmental resistance and can achieve high dimensional stability. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic perspective view showing the configuration of a microfibrillated cellulose article according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of the microfibrillated cellulose article shown in FIG. [Diagram 3] FIG. 3 is a flow chart showing typical steps in a method for producing a microfibrillated cellulose body according to one embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic cross-sectional view showing an example of the first preformed sheet. [Diagram 5] FIG. 5 is a schematic cross-sectional view of the first preformed sheet shown in FIG. [Figure 6] FIG. 6 is a schematic cross-sectional view showing the state in which the first preformed sheet is swelled with water. [Figure 7] FIG. 7 is a schematic cross-sectional view showing a state in which the product is immersed in a solution containing a melamine resin. [Figure 8] FIG. 8 is a schematic cross-sectional view showing the process of performing the heat press. [Figure 9] FIG. 9 is a schematic cross-sectional view of four sheets of microfibrillated cellulose-containing compositions stacked together and heat-pressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Description of the embodiments of the present disclosure] Hereinafter, an embodiment of the present invention will be described. The microfibrillated cellulose molded article according to the present disclosure is composed of microfibrillated cellulose and melamine resin. The content of the melamine resin is 20.0 mass% or more. The water absorption rate when immersed in water at 20°C for 24 hours is 1.6% or less.
[0010] The microfibrillated cellulose molded body (hereinafter sometimes simply referred to as "molded body") according to the present disclosure is composed of microfibrillated cellulose and melamine resin. Such a microfibrillated cellulose molded body can have good environmental resistance because the only material other than the microfibrillated cellulose is melamine resin. Furthermore, in such a microfibrillated cellulose molded body with a very high melamine resin content, the melamine resin is sufficiently embedded between the fibers of the microfibrillated cellulose, so there are very few gaps between the fibers through which moisture can penetrate. As a result, even if exposed to a humid environment, it hardly absorbs moisture. Therefore, high dimensional stability can be achieved.
[0011] The microfibrillated cellulose molded body according to the present disclosure is composed of microfibrillated cellulose, melamine resin, and dye. The content of the melamine resin is 20.0% by mass or more. The content of the dye is 0.3% by mass or more. The water absorption rate when immersed in water at 20°C for 24 hours is 0.6% or less. Recently, there has been a demand for coloring the microfibrillated cellulose molded body in various colors. Melamine resin is colorless and transparent, and coloring by dyes can be easily achieved. By adopting the microfibrillated cellulose molded body having the above-mentioned configuration, it is possible to obtain a microfibrillated cellulose molded body colored in a desired color while achieving good environmental resistance and high dimensional stability.
[0012] In the microfibrillated cellulose article, the content of the melamine resin may be 31% by mass or less, which makes it possible to more reliably achieve good environmental resistance and high dimensional stability.
[0013] The microfibrillated cellulose article may have a water absorption rate of 0.6% or less, which allows the microfibrillated cellulose article to achieve even higher dimensional stability.
[0014] The microfibrillated cellulose molded article according to the present disclosure is in the form of a plate and is composed of microfibrillated cellulose and melamine resin. The content of the melamine resin is 20.0% by mass or more. The dimensional change in the thickness direction when immersed in water at 20°C for 24 hours is 0.6% or less.
[0015] Such a microfibrillated cellulose molded article can absorb moisture even in a high humidity environment, and the risk of it swelling, resulting in insufficient strength, or warping can be reduced, making it possible to provide a microfibrillated cellulose molded article with improved convenience.
[0016] The microfibrillated cellulose molded article according to the present disclosure is in the form of a plate and is composed of microfibrillated cellulose, melamine resin, and a dye. The content of the melamine resin is 20.0% by mass or more. The dimensional change in the thickness direction when immersed in water at 20°C for 24 hours is 0.2% or less.
[0017] Such a microfibrillated cellulose molded article has good colorability, and even in a high humidity environment, it absorbs moisture and swells, reducing the risk of strength loss or warping, making it possible to provide a microfibrillated cellulose molded article with improved usability.
[0018] The microfibrillated cellulose article may have a flexural modulus of 13.0 GPa or more. Such a microfibrillated cellulose article can be made less prone to deformation, and can be more convenient as a material.
[0019] The microfibrillated cellulose body may have a longitudinal dimensional change of 0.1% or less when immersed for 24 hours in water at 20° C. Such a microfibrillated cellulose body can achieve high dimensional stability and can be made more convenient as a material.
[0020] The method for producing a microfibrillated cellulose molded body according to the present disclosure is a method for producing a microfibrillated cellulose molded body composed of microfibrillated cellulose and melamine resin, and includes the steps of preparing a first preformed sheet composed of microfibrillated cellulose and 0% to 10% by mass of water, exposing the first preformed sheet to water for one hour or more to cause it to swell and obtain a second preformed sheet, replacing the water contained in the second preformed sheet with a solution containing melamine resin to obtain a third preformed sheet, drying the obtained third preformed sheet, and heat pressing the dried third preformed sheet in the thickness direction at a temperature of 120°C to 200°C and a pressure of 1 MPa to 10 MPa.
[0021] The method for producing a microfibrillated cellulose molded body according to the present disclosure includes the steps of preparing a first preformed sheet composed of microfibrillated cellulose and water of 0% by mass or more and 10% by mass or less, exposing the first preformed sheet to water for 1 hour or more to swell the first preformed sheet, and obtaining a second preformed sheet. Since water is a molecule with high affinity for cellulose, it can sufficiently penetrate between the fibers of the microfibrillated cellulose compressed in the first preformed sheet, and can sufficiently swell the first preformed sheet to obtain a second preformed sheet. Next, the method includes the step of replacing the water contained in the second preformed sheet with a solution containing a melamine resin to obtain a third preformed sheet. Here, since the second preformed sheet is sufficiently swollen by the water and the intervals between the fibers of the microfibrillated cellulose are widened, the solution containing the melamine resin can be sufficiently permeated between the fibers of the microfibrillated cellulose. That is, the water between the fibers of the microfibrillated cellulose can be replaced with the solution containing the melamine resin, and the solution containing the melamine resin can be disposed between the fibers of the microfibrillated cellulose. Then, the product is dried and heat-pressed at a temperature of 120°C to 200°C under a pressure of 1 MPa to 10 MPa in the thickness direction to heat-set the melamine resin between the fibers of the microfibrillated cellulose to obtain a microfibrillated cellulose molded product. In such a microfibrillated cellulose molded product, the melamine resin is sufficiently permeated between the fibers, so that the gaps between the fibers into which moisture can enter can be extremely reduced. As a result, even if exposed to a humid environment, the product hardly absorbs moisture. Therefore, high dimensional stability can be achieved. In addition, since the heat-pressing can be performed at the above-mentioned temperature and pressure, a high pressure such as 100 MPa is not required, and the productivity is good.
[0022] In the above-mentioned method for producing a microfibrillated cellulose body, the step of hot pressing may include a step of hot pressing a plurality of third preformed sheets stacked together, which makes it easier to obtain a microfibrillated cellulose body having a desired thickness and also allows the melamine resin to penetrate more thoroughly into the microfibrillated cellulose body, thereby improving dimensional stability.
[0023] In the above-mentioned method for producing a microfibrillated cellulose article, the step of obtaining the second preformed sheet may include a step of immersing the first preformed sheet in water stored in a container for 1.5 hours to 24 hours, thereby enabling swelling with water to be carried out more efficiently.
[0024] In the method for producing a microfibrillated cellulose body, the content of the melamine resin in the third preformed sheet may be 20.0% by mass or more and 31.0% by mass or less, thereby realizing high dimensional stability while maintaining high strength of the microfibrillated cellulose.
[0025] [Details of the embodiment of the present disclosure] Next, the configuration of a microfibrillated cellulose body according to an embodiment of the present disclosure will be described. Fig. 1 is a schematic perspective view showing the configuration of a microfibrillated cellulose body according to one embodiment of the present disclosure. Fig. 2 is a schematic cross-sectional view of the microfibrillated cellulose body shown in Fig. 1.
[0026] 1 and 2, a microfibrillated cellulose body 11 according to an embodiment of the present disclosure may be, for example, in the form of a plate. The thickness T1 of the body 11 may be, for example, 0.1 mm or more and 2.0 mm or less. The thickness of the body 11 is the length from one surface 12a in the thickness direction (Z direction) of the microfibrillated cellulose body 11 to the other surface 12b in the thickness direction. The horizontal direction (width direction) of the body 11 is indicated by the X direction, and the vertical direction (depth direction) of the body 11 is indicated by the Y direction.
[0027] The microfibrillated cellulose molded body 11 is composed of microfibrillated cellulose and melamine resin. Since the only material other than the microfibrillated cellulose is the melamine resin, this microfibrillated cellulose molded body can have good environmental resistance.
[0028] The microfibrillated cellulose used in the microfibrillated cellulose article 11 according to the present disclosure is also called cellulose nanofiber, and is a microfibrillated cellulose fiber. Examples of raw materials for microfibrillated cellulose are plant-derived materials such as wood and cotton, and examples of animal-derived materials may include those derived from chitin and chitosan.
[0029] The fiber diameter of the microfibrillated cellulose used is 10 nm or more and 1000 nm or less. This allows the microfibrillated cellulose in the molded body 11 to be more densely entangled. Therefore, the strength of the obtained molded body 11 can be increased.
[0030] As the melamine resin, any known condensation product obtained by condensing melamine or its derivatives with formaldehyde and consisting of a monomer and a dimer or higher polymer can be used. Examples of the melamine derivative include derivatives having an imino group, a methylol group, or an alkoxymethyl group such as a methoxymethyl group or a butoxymethyl group. In addition, a compound obtained by reacting a melamine derivative having a methylol group with an alcohol to partially or completely etherify it can also be used as a monomer.
[0031] The content of the melamine resin is 20.0% by mass or more of the total. The content of the melamine resin is preferably 31.0% by mass or less of the total. The content of the microfibrillated cellulose is preferably 69.0% by mass or more and 80.0% by mass or less of the total. By setting the content of the microfibrillated cellulose to 69.0% by mass or more and 80.0% by mass or less, sufficient strength of the molded body 11 can be ensured. Furthermore, by setting the content of the melamine resin to 20.0% by mass or more, the melamine resin can be sufficiently permeated between the fibers, reducing the gaps between the fibers, and high dimensional stability can be more reliably achieved. Furthermore, by setting the content of the melamine resin to 31.0% by mass or less, high dimensional stability can be more reliably achieved while improving environmental resistance.
[0032] Here, the water absorption rate of the molded body 11 is 1.6% or less when immersed in water at 20°C for 24 hours. Such a molded body 11 can reduce the risk of absorbing moisture and swelling, resulting in insufficient strength, or warping, even in a high humidity environment. Therefore, the molded body 11 can be made more convenient. The water absorption rate may be 0.6% or less. Such a molded body 11 can achieve even higher dimensional stability.
[0033] Furthermore, the dimensional change rate of the molded body 11 in the thickness direction when immersed in water at 20°C for 24 hours (hereinafter, sometimes referred to as "thickness change rate") is 0.6% or less. Such a molded body 11 can reduce the risk of absorbing moisture and swelling, causing insufficient strength, or warping, even in a high humidity environment. Therefore, the molded body 11 can be made more convenient. The thickness change rate may be 0.4% or less. Such a molded body 11 can achieve even higher dimensional stability.
[0034] Furthermore, the dimensional change rate of the molded body 11 in the length direction when immersed in water at 20°C for 24 hours (hereinafter, sometimes referred to as "length change rate") is 0.1% or less. Such molded body 11 can reduce the risk of absorbing moisture and swelling, resulting in insufficient strength, or warping, even in a high humidity environment. Therefore, the molded body 11 can be made more convenient. The length change rate may be 0.06% or less. Such molded body 11 can achieve even higher dimensional stability.
[0035] Furthermore, the content of melamine resin in molded body 11 is 20.0% by mass or more and 31.0% by mass or less, so that molded body 11 can be made more convenient.
[0036] The molded body 11 has a flexural modulus of 13.0 GPa or more. Such molded body 11 can achieve high strength and can further improve the convenience as a material. The flexural modulus may be 14.0 GPa or more.
[0037] The molded body 11 has a bending strength of 210 MPa or more. Such molded body 11 can achieve high strength and can further improve the convenience as a material. The bending strength may be 230 MPa or more.
[0038] The molded article may be composed of microfibrillated cellulose, melamine resin, and dye. The content of the melamine resin may be 20.0% by mass or more. The content of the dye may be 0.3% by mass or more. The water absorption rate when immersed in water at 20°C for 24 hours may be 0.6% or less. Recently, there has been a demand for coloring the microfibrillated cellulose molded article in various colors. Melamine resin has a relatively high transparency, and coloring by dyes can be easily realized. By adopting the molded article of the above configuration, it is possible to obtain a molded article colored in a desired color while realizing good environmental resistance and high dimensional stability.
[0039] Next, a description will be given of a manufacturing method for producing such a molded article 11. Fig. 3 is a flow chart showing typical manufacturing steps in the manufacturing method for a microfibrillated cellulose molded article according to one embodiment of the present disclosure.
[0040] 3, first, a first preformed sheet is prepared (step S11 in FIG. 3, hereinafter "step" will be omitted). The first preformed sheet is composed of microfibrillated cellulose and 0% to 10% by mass of water.
[0041] FIG. 4 is a schematic cross-sectional view showing an example of the first preformed sheet. FIG. 5 is a schematic cross-sectional view of the first preformed sheet shown in FIG. 4. Referring to FIG. 4 and FIG. 5, the first preformed sheet 21a is in a sheet shape, and the thickness T2 is, for example, 0.1 mm or more and 0.5 mm or less. The first preformed sheet 21a can be obtained, for example, as follows. First, a dispersion liquid in which microfibrillated cellulose is dispersed in water is prepared, and the dispersion liquid is suction filtered to form a sheet shape, thereby obtaining a microfibrillated cellulose-containing composition having a moisture content of, for example, 65% by mass or more and 85% by mass or less. The microfibrillated cellulose-containing composition is compressed in the thickness direction to remove moisture to a certain extent, thereby obtaining the first preformed sheet 21a having a solid content of 90% by mass or more and 100% by mass or less. In the same manner, a plurality of first preformed sheets are obtained.
[0042] Next, the first preformed sheet 21a is exposed to water for at least one hour to cause it to swell, thereby obtaining a second preformed sheet (S12). Fig. 6 is a schematic cross-sectional view showing the state in which the first preformed sheet 21a is swollen by water.
[0043] Referring to FIG. 6, first, in this step, a container 13 storing water 14 is prepared. Then, the first preformed sheet 21a is immersed. Specifically, the first preformed sheet 21a is put into the water 14 in the container 13 so that the entire surface of the first preformed sheet 21a is immersed in the water 14. In this way, the first preformed sheet 21a is exposed to water. Thereafter, it is left as it is until a predetermined time has passed. Specifically, it is immersed in water 14 at a water temperature of 20°C and left for 24 hours. Then, the first preformed sheet 21a swells with the water 14. That is, the water 14 penetrates between the fibers of the microfibrillated cellulose constituting the microfibrillated cellulose-containing composition. In this way, the second preformed sheet is obtained. The second preformed sheet swells mainly in the thickness direction. The step of obtaining the second preformed sheet may include a step of immersing the first preformed sheet in water stored in a container for 72 hours or less. In this way, swelling with water can be carried out more efficiently.
[0044] Here, the thickness of the second preformed sheet may be 160% or more of the thickness of the first preformed sheet 21a, which makes it easier to impregnate the sheet with melamine resin and more reliably achieves high dimensional stability.
[0045] Next, the water contained in the second preformed sheet is replaced with a solution containing a melamine resin to obtain a third preformed sheet (S13). Fig. 7 is a schematic cross-sectional view showing a state in which the sheet is immersed in a solution containing a melamine resin.
[0046] 7, in this step, a container 15 is prepared that stores a solution 16 containing a melamine resin. Then, the second preformed sheet 23a is immersed in the solution. Specifically, the second preformed sheet 23a is placed in the solution 16 in the container 15 so that the entire surface of the second preformed sheet 23a is immersed in the solution 16.
[0047] Here, for example, an aqueous solution of melamine resin is used as the solution 16 containing melamine resin. That is, the solution 16 containing melamine resin contains water. In addition to water, water-soluble organic solvents such as methanol, ethanol, and isopropanol can be used. Furthermore, a mixture of water and a water-soluble organic solvent can be used.
[0048] Next, the obtained third preformed sheet is dried (S14). The drying step is carried out, for example, by leaving it at room temperature (25° C.) for 24 hours.
[0049] Next, the dried third preformed sheet is heat-pressed at a temperature of 120°C to 200°C and a pressure of 1 MPa to 10 MPa in the thickness direction (S15). In this case, the heat-pressing step includes a step of stacking and heat-pressing a plurality of third preformed sheets. Fig. 8 is a schematic cross-sectional view of the heat-pressing step.
[0050] 8, the two prepared third preformed sheets 24a, 24b are placed between a pair of metal plates 17a, 17b heated to a temperature of 120° C. to 200° C. in a stacked manner. Then, a pressure of 1 MPa to 10 MPa is applied in the direction indicated by the arrow D1. Specifically, for example, the temperature of the metal plates 17a, 17b is set to 150° C., and a pressure of 6.5 MPa is applied for 1.5 hours.
[0051] In this manner, the microfibrillated cellulose molded body 11 according to the present disclosure shown in FIG. 1 is obtained. The microfibrillated cellulose molded body 11 manufactured by the manufacturing method of the microfibrillated cellulose molded body 11 is composed of microfibrillated cellulose and melamine resin. Since the only material other than the microfibrillated cellulose is melamine resin, the microfibrillated cellulose molded body 11 can have good environmental resistance. The manufacturing method of the microfibrillated cellulose molded body includes the steps of preparing a first preformed sheet 21a composed of microfibrillated cellulose and 0% to 10% by mass of water, exposing the first preformed sheet 21a to water for 1 hour or more to cause it to swell, and obtaining a second preformed sheet 23a. Since water is a molecule with high affinity for cellulose, it can sufficiently penetrate between the fibers of the microfibrillated cellulose compressed in the first preformed sheet 21a, and sufficiently swell the first preformed sheet 21a to obtain the second preformed sheet 23a. Next, the method includes a step of replacing the water contained in the second preformed sheet with a solution containing melamine resin to obtain a third preformed sheet. Here, the second preformed sheet is sufficiently swollen by the water, and the gaps between the fibers of the microfibrillated cellulose are widened, so that the solution containing melamine resin can be sufficiently permeated between the fibers of the microfibrillated cellulose. That is, the water between the fibers of the microfibrillated cellulose can be replaced with a solution containing melamine resin, and the solution containing melamine resin can be disposed between the fibers of the microfibrillated cellulose. Then, the sheet is dried and heat-pressed at a temperature of 120°C to 200°C and a pressure of 1 MPa to 10 MPa in the thickness direction to thermally cure the melamine resin between the fibers of the microfibrillated cellulose, thereby obtaining a microfibrillated cellulose molded body. In such a microfibrillated cellulose molded body, the melamine resin is sufficiently permeated between the fibers, so that the gaps between the fibers into which moisture can enter can be extremely reduced. In this way, even if the microfibrillated cellulose molded body is exposed to a humid environment, it hardly absorbs moisture. Therefore, high dimensional stability can be achieved.Furthermore, since the heat press can be performed at the above-mentioned temperature and pressure, a high pressure such as 100 MPa is not required, and the productivity is good.
[0052] As described above, such a method for producing a microfibrillated cellulose article has good productivity and can achieve high dimensional stability of the obtained microfibrillated cellulose article.
[0053] In this case, since the process includes a step of stacking and hot pressing multiple third preformed sheets 24a, 24b, it is possible to easily obtain a microfibrillated cellulose body 11 having the desired thickness, and also to allow the melamine resin to penetrate more deeply into the interior of the microfibrillated cellulose body 11, thereby improving dimensional stability.
[0054] The manufacturing method may be as follows. The step of preparing the first preformed sheet includes a step of stacking and hot pressing a plurality of sheet-shaped microfibrillated cellulose-containing compositions made of microfibrillated cellulose to obtain the first preformed sheet. Fig. 9 is a schematic cross-sectional view of four sheets of microfibrillated cellulose-containing compositions stacked and hot pressed.
[0055] 9, four sheets of microfibrillated cellulose-containing compositions 25a, 25b, 25c, and 25d are stacked and arranged between metal plates 18a and 18b, and pressure is applied in the direction indicated by arrow D2 to obtain a first preformed sheet. The preformed sheet thus obtained is used to obtain a second preformed sheet in the same manner as described above. After obtaining a third preformed sheet, heat pressing is performed to obtain a molded body 11.
[0056] In this case, a microfibrillated cellulose article having a desired thickness can be easily obtained, leading to improved productivity.
[0057] In the above embodiment, the first preformed sheet is exposed to water and swelled by immersing it in water stored in a container, but this is not limited to the above, and swelling with water may also be achieved by exposing the first preformed sheet to running water.
[0058] In the above embodiment, when the microfibrillated cellulose body further contains a dye, a water-soluble dye may be added to a solution containing melamine resin and adjusted to a desired dye content, thereby producing a microfibrillated cellulose body further containing a dye.
[0059] In the above embodiment, urea-melamine resin may be used in place of the melamine resin.
[0060] In the above embodiment, the first preformed sheet is prepared, the first preformed sheet is exposed to water for one hour or more to swell the sheet to obtain the second preformed sheet, and the water contained in the second preformed sheet is replaced with a solution containing melamine resin to obtain the third preformed sheet, but this is not limiting and the step of obtaining the second preformed sheet may be omitted. That is, after the first preformed sheet is prepared, the sheet may be exposed to a solution containing melamine resin without being exposed to water, and the solution containing melamine resin may be allowed to permeate between the fibers of the microfibrillated cellulose to obtain the third preformed sheet. Sample 6 described later is produced by this method. EXAMPLES
[0061] Molded articles were molded according to the compositions and methods shown in Samples 1 to 10, and evaluation tests were carried out. The evaluation results are shown in Table 1. Samples 1 to 7 are within the scope of the present invention. Samples 8 to 10 are outside the scope of the present invention.
[0062] (Sample 1) Microfibrillated cellulose ("BiNFi-S (Binfis) BMa10010" manufactured by Sugino Machine Co., Ltd.: fiber diameter 10 nm to 50 nm or less) dispersed in water at a concentration of 10% by mass was prepared. The mixture was then diluted with water to 1% by mass, and the water was then removed by filtration until the water content reached 85% by mass, to obtain a sheet-like MFC-containing composition having a thickness of 2.0 mm.
[0063] Next, one sheet of the MFC-containing composition is applied to a substrate with a basis weight of 47 g / cm 2 The sheet was sandwiched between two sheets of glass nonwoven fabric, sandwiched between two stainless steel metal plates, and heated and pressurized at 150°C for 2 hours to obtain a first preformed sheet. The pressure was increased stepwise from 0.5 MPa, and finally reached 4 MPa. The thickness of the obtained first preformed sheet was 0.4 mm, and the moisture content was 0% by mass or more and 10% by mass or less.
[0064] The first preformed sheet was immersed in water at a temperature of 20° C. for 24 hours to obtain a second preformed sheet, which had a thickness of 0.7 mm.
[0065] Next, the second preformed sheet was immersed for 24 hours in a melamine resin solution (solid content 40% by mass) prepared by dissolving a water-soluble methylolmelamine resin ("Nikaredin S-260" manufactured by Nippon Carbide Industries Co., Ltd.) in warm water at 40°C, to obtain a third preformed sheet.
[0066] The obtained third preformed sheet was then dried for 24 hours at room temperature (25° C.) Two dried third preformed sheets were sandwiched between two stainless steel metal plates and heated and pressurized at 150° C. and a pressure of 6.5 MPa for 1 hour to obtain a molded body composed of microfibrillated cellulose and melamine resin.
[0067] The obtained molded product was milky white, had a thickness of 1.0 mm, and a density of 1.41 g / cm 3The content of melamine resin was 30.3% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 14.2 GPa and the flexural strength was 247 MPa. When immersed in water at 20°C for 24 hours, the water absorption rate was 0.6% and the dimensional change rate in the thickness direction was 0.3%. When immersed in water at 20°C for 24 hours, the dimensional change rate in the length direction (hereinafter sometimes referred to as "length change rate") was 0.06%.
[0068] The water absorption rate was determined by the following method in accordance with "JIS A5905." A test piece (10 cm x 10 cm) of the molded body that had been cured for 72 hours or more in an environment of 20°C temperature and 65% relative humidity was immersed in water at 20°C for 24 hours. The water absorption rate was then calculated by the following formula (1) using the measured mass (W1) of the test piece before immersion and the mass (W2) of the test piece after immersion.
[0069] Water absorption rate (%)=((W2-W1) / W1)×100...(1)
[0070] The thickness change rate was determined by the following method in accordance with "JIS A5905." A test piece (10 cm x 10 cm) of the molded body that had been cured for 72 hours or more in an environment at a temperature of 20°C and a relative humidity of 65% was immersed in water at 20°C for 24 hours. The thickness change rate was then calculated by the following formula (2) using the measured thickness (T1) of the test piece before immersion and the thickness (T2) of the test piece after immersion.
[0071] Thickness change rate (%) = ((T2-T1) / T1) × 100 (2)
[0072] The length change rate was determined by the following method in accordance with "JIS A5905." A test piece (10 cm x 10 cm) of the molded body that had been cured in an environment of 20°C and 65% relative humidity for 72 hours or more was immersed in water at 20°C for 24 hours. The length change rate was calculated by the following formula (3) using the measured side length (L1) of the test piece before immersion and the side length (L2) of the test piece after immersion. Here, for the length (L1) and length (L2) of the test piece, the one with the larger change rate in the vertical direction or the horizontal direction was used.
[0073] Length change rate (%) = ((L2-L1) / L1) × 100 (3)
[0074] The molding was also measured for flexural modulus, flexural strength and density in accordance with JIS-K6911. The same was true for the measurements of the following samples.
[0075] (Sample 2) A molded product was obtained in the same manner as in Sample 1, except that the third preformed sheet was obtained by immersing the sheet in an aqueous melamine resin solution (solid content: 40% by mass) for 1.5 hours. The molded product thus obtained was milky white, had a thickness of 0.95 mm, and a density of 1.39 g / cm. 3 The content of melamine resin was 21.6% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 15.4 GPa and the flexural strength was 225 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 1.6%, and the length change rate and thickness change rate were 0.09% and 0.6%, respectively.
[0076] (Sample 3) A molded product was obtained in the same manner as in Sample 1, except that the third preformed sheet was obtained by immersing the sheet in an aqueous melamine resin solution (solid content: 40% by mass) for 3 hours. The molded product thus obtained was milky white, had a thickness of 1.0 mm, and a density of 1.41 g / cm 3The content of melamine resin was 25.7% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 15.1 GPa and the flexural strength was 213 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 1.1%, and the length change rate and thickness change rate were 0.07% and 0.4%, respectively.
[0077] (Sample 4) A molded body was obtained in the same manner as in Sample 1, except that eight third preformed sheets were laminated and molded under heat and pressure. The obtained molded body was milky white, had a thickness of 4.0 mm, and a density of 1.41 g / cm. 3 The content of melamine resin was 30.3% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 14.2 GPa and the flexural strength was 247 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 0.3%, and the length change rate and thickness change rate were 0.04% and 0.2%, respectively.
[0078] (Sample 5) A molded body was obtained in the same manner as in Sample 1, except that 20 sheets of the third preformed sheet were laminated and molded under heat and pressure. The obtained molded body was milky white, had a thickness of 10.0 mm, and a density of 1.41 g / cm. 3 The content of melamine resin was 30.3% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 14.2 GPa and the flexural strength was 247 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 0.2%, and the length change rate and thickness change rate were 0.02% and 0.2%, respectively.
[0079] (Sample 6) A molded body was obtained in the same manner as in Sample 1, except that the first preformed sheet was not immersed in water at a temperature of 20° C. The obtained molded body was milky white, had a thickness of 1.0 mm, and a density of 1.42 g / cm 3The content of melamine resin was 29.1% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 13.7 GPa and the flexural strength was 218 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 0.8%, and the length change rate and thickness change rate were 0.09% and 0.4%, respectively.
[0080] (Sample 7) A molded product was obtained in the same manner as Sample 1, except that 1 part by weight of a water-soluble black dye (Direct Fast Black B 300% manufactured by Okamoto Senryo Co., Ltd.) was further added to the melamine resin solution. The obtained molded product was black in color, had a thickness of 1.0 mm, and a density of 1.39 g / cm. 3 The content of melamine resin was 28.8% by mass. The content of dye was 0.3% by mass. In an environment of 20°C temperature and 65% relative humidity, the flexural modulus was 13.4 GPa and the flexural strength was 230 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 0.6%, and the length change rate and thickness change rate were 0.02% and 0.2%, respectively.
[0081] (Sample 8) Two sheets of the microfibrillated cellulose-containing composition, each having a moisture content of 85% by mass and a thickness of 2.5 mm, were laminated and molded under heat and pressure at a press temperature of 150°C, a press pressure of 4 MPa, and a press time of 2 hours to obtain a molded product. The obtained molded product was milky white, had a thickness of 1.0 mm, and a density of 1.33 g / cm. 3 In addition, under an environment of 20°C temperature and 65% relative humidity, the flexural modulus was 10.5 GPa and the flexural strength was 146 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 55.8%, and the length change rate and thickness change rate were 0.94% and 62.0%, respectively.
[0082] (Sample 9) A molded product was obtained in the same manner as in Sample 1, except that a phenolic resin was used instead of the melamine resin. The molded product obtained was brown in color, had a thickness of 1.0 mm, and had a density of 1.40 g / cm. 3 The content of phenol resin was 26.5% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 11.0 GPa and the flexural strength was 245 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 1.9%, and the length change rate and thickness change rate were 0.19% and 1.4%, respectively.
[0083] (Sample 10) A molded product was obtained in the same manner as in Sample 1, except that the resin impregnation time was 0.2 hours. The molded product obtained was milky white, had a thickness of 0.9 mm, and a density of 1.38 g / cm. 3 The content of melamine resin was 11.7% by mass. In addition, in an environment of a temperature of 20°C and a relative humidity of 65%, the flexural modulus was 13.8 GPa and the flexural strength was 218 MPa. When immersed in water at 20°C for 24 hours, the water absorption was 2.0%, and the length change rate and thickness change rate were 0.12% and 2.0%, respectively.
[0084] [Table 1]
[0085] Referring to Table 1, in each of Samples 1 to 7, the content of melamine resin is 20.0% by mass or more, and the water absorption is 1.6% or less. Specifically, the content of phenol resin is 31.0% by mass or less. In addition, the dimensional change rate in the thickness direction when immersed in water at 20° C. for 24 hours is 1.6% or less. In addition, the dimensional change rate in the length direction when immersed in water at 20° C. for 24 hours is 0.10% or less. In addition, the flexural modulus is 13.0 GPa or more. In addition, the flexural strength is 210 MPa or more. In addition, the color of Samples 1 to 6 is milky white, and the color of Sample 7 is black. In Sample 7, the color of the black dye is fully expressed.
[0086] In contrast, Sample 8 does not contain resin, and has a water absorption rate of 55.8%, a thickness change rate of 62.0%, and a length change rate of 0.94%. It is considered that such a molded body has a large water absorption rate, thickness change rate, and length change rate because no resin is present at the interface of the laminated layers of the molded body and water penetrates between the fibers that make up the molded body and swells. In addition, the flexural modulus and flexural strength are also lower than those of Samples 1 to 7.
[0087] For sample 9, phenol resin is used instead of melamine resin, but the water absorption rate is 1.9%, the thickness change rate is 1.4%, and the length change rate is 0.19%. For such a molded body, the laminated interface of the molded body cannot be sufficiently wetted with phenol resin, and the adhesive strength between the layers is weakened, which is considered to increase the water absorption rate, the thickness change rate, and the length change rate. In addition, the flexural modulus is also lower than that of samples 1 to 7.
[0088] For sample 10, the resin impregnation time of the melamine resin is short, the resin content is 11.7 mass%, the water absorption rate is 2.0%, the thickness change rate is 2.0%, and the length change rate is 0.12%. For such a molded body, it is considered that the interface of the laminated layers of the molded body cannot be sufficiently wetted with the melamine resin, the adhesive strength between the layers is weakened, and the water absorption rate, the thickness change rate, and the length change rate are large.
[0089] It should be understood that the embodiments disclosed herein are illustrative in all respects and are not limiting in any respect. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]
[0090] 11 microfibrillated cellulose body, 12a, 12b surfaces, 13, 15 container, 14 water, 16 solution, 17a, 17b, 18a, 18b metal plates, 21a first preformed sheet, 23a second preformed sheet, 24a, 24b third preformed sheet, 25a, 25b, 25c, 25d microfibrillated cellulose-containing composition.
Claims
1. It is composed of microfibrillated cellulose and melamine resin, The content of the melamine resin is 20.0% by mass or more and 30.3% by mass or less, A microfibrillated cellulose molding having a water absorption rate of 1.6% or less when immersed in water at 20°C for 24 hours.
2. It is composed of microfibrillated cellulose, melamine resin, and dye, The content of the melamine resin is 20.0% by mass or more and 28.8% by mass or less, The content of the dye is 0.3% or more, A microfibrillated cellulose molding having a water absorption rate of 0.6% or less when immersed in water at 20°C for 24 hours.
3. 3. The microfibrillated cellulose molded article according to claim 1, wherein the water absorption rate is 0.6% or less.
4. The sheet is made of microfibrillated cellulose and melamine resin. The content of the melamine resin is 20.0% by mass or more and 30.3% by mass or less, A microfibrillated cellulose molding having a dimensional change in the thickness direction of 0.6% or less when immersed in water at 20°C for 24 hours.
5. The sheet is made of microfibrillated cellulose, melamine resin, and dye. The content of the melamine resin is 20.0% by mass or more and 28.8% by mass or less, A microfibrillated cellulose molding having a dimensional change in the thickness direction of 0.2% or less when immersed in water at 20°C for 24 hours.
6. 6. The microfibrillated cellulose article according to claim 4, which has a flexural modulus of 13.0 GPa or more.
7. 6. The microfibrillated cellulose article according to claim 4, which has a dimensional change in the longitudinal direction of 0.1% or less when immersed in water at 20° C. for 24 hours.
Citation Information
Patent Citations
Water-blocking and flame-retardant aluminum-plastic film for lithium battery soft package and preparation method thereof
CN109532147A
Method and apparatus for defibrillating cellulose fibers
JP2012530857A
Cellulose nanofiber-containing resin composition, and molding thereof
JP2020050780A
Molded article of microfibrillar cellulose and its manufacturing method
JP2009096167A
High-strength materials using cellulose microfibrils
JP3641690B2